The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1371/journal.pone.0003620
|View full text |Cite
|
Sign up to set email alerts
|

Common Genetic Origins for EEG, Alcoholism and Anxiety: The Role of CRH-BP

Abstract: The resting EEG is a dynamic index of cortical activation, cognitive function and consciousness and is therefore an intermediate phenotype for many behaviors in which arousal is implicated such as anxiety and alcoholism. We performed a dense whole genome linkage scan using 3878 unlinked SNPs in a large pedigree derived from a population isolate sample of 328 Plains American Indians. Alpha (8–13 Hz), theta (4–8 Hz) and beta (13–30 Hz) EEG power was heritable (0.58–0.27) and stable over a 2 year period (r = 0.82… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
87
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 60 publications
(66 reference statements)
9
87
1
Order By: Relevance
“…Alleles significant (but subthreshold) for association with increased θ power were underrepresented in individuals with AUD. Reduced θ power in alcoholics had been reported for this dataset (15). The present data indicate a relationship between SGIP1 genotype and AUD.…”
supporting
confidence: 81%
See 3 more Smart Citations
“…Alleles significant (but subthreshold) for association with increased θ power were underrepresented in individuals with AUD. Reduced θ power in alcoholics had been reported for this dataset (15). The present data indicate a relationship between SGIP1 genotype and AUD.…”
supporting
confidence: 81%
“…SGIP1 and ST6GALNAC3 lie within a linkage peak on chr 1p (95-115 cM), linked to β2 EEG spectral power (16)(17)(18)(19)(20) in the COGA (27,28). UGDH, LIAS, RPL9, and KLB lie in a region of chr 4 previously linked to EEG in this Plains Indian dataset (15), together with an additional Native American population (29) and in the COGA dataset (30). Additionally, the study has identified BICD1 located on chr 12p11 as a candidate gene for resting α power variability.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…It is likely, however, that multiple genes contribute to "alpha phenotypes", and a few candidate genes were indeed found to affect alpha oscillations. So, recent genetic polymorphism studies indicated that the gene on chromosome 5q13-14 of corticotrophin releasing hormone-binding protein (CRH-BP) modulates alpha power in isolated Plains American Indians and Caucasians [85]. Moreover, a functional variation in exon 7 of the gene on chromosome 6 encoding the human GABAB receptor (GABABR1) also influences EEG voltage in the alpha range [86].…”
Section: The Alpha Activity Phenomena Hypothesismentioning
confidence: 99%